STUDI WINDOW-TO-WALLRATIO PADA KANTOR PEMERINTAH DI JAKARTA SELATAN - Melisa Imam Dwiana; Agus Budi Purnomo; Nuzuliar Rahmah (Ide dan Dialog Desain Indonesia (Idealog), 2020)
Government offices are buildings that are expected to be a good example of energy-efficient buildings. Many efforts can be done to save energy, one of them is to pay attention to the design of the facade. Windows as openings in the facade can be arranged so that the sun's heat does not result in an increase of energy to cool the room also reducing the use of lights during the day. One od the aspect that can be used to assess window opening performance is Window-to-Wall Ratio (WWR). The ratio is obtained by dividing the total opening area of the wall using glass by the total surface area of the building envelope. The purpose of this research is to study the value of WWR from government office buildings in South Jakarta. This study use front elevation of 20 government office buildings in South Jakarta as a case study. The results of this study are the average WWR value of government offices which were later compared to the average WWR of similar offices from other literature. From the results of the study, an average WWR value of 24.6% was obtained, which is still in the range of WWR in other studies.Keywords : Energy Saving, Building Envelope, Government Office, Window-to-Wall Ratio (WWR)